A Primer in Interdisciplinarity: J. Wentzel van Huyssteen and the Post-Foundational Approach - Green, Erin (Toronto journal of theology, 2011)
Understanding the relationship between theological and scientific reasoning is a longstanding problem in the history of Western theology. Two paradigmatic modes of thinking—foundationalism and non-foundationalism—have shaped this discourse and have on the whole hindered, in J. Wentzel van Huyssteen's estimation, fruitful interdisciplinary dialogue. In response to the unchecked affinity for scientific rationality of the former and the relativism of the latter, van Huyssteen proposes a third way to understand interdisciplinary interaction between theology and the natural sciences—post-foundationalism. This approach promises to open a new way of understanding human reasoning by placing interdisciplinary concerns at its core and giving theology a strong public voice. This essay surveys some aspects of van Huyssteen's post-foundationalism, including an orientation to his understanding of foundationalism and non-foundationalism and their interdisciplinary potential.